2017
DOI: 10.3390/plants6010014
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Ozone and Drought on the Physiology and Membrane Lipids of Two Cowpea (Vigna unguiculata (L.) Walp) Cultivars

Abstract: The interactive effects of drought and ozone on the physiology and leaf membrane lipid content, composition and metabolism of cowpea (Vigna unguiculata (L.) Walp.) were investigated in two cultivars (EPACE-1 and IT83-D) grown under controlled conditions. The drought treatment (three-week water deprivation) did not cause leaf injury but restricted growth through stomatal closure. In contrast, the short-term ozone treatment (130 ppb 12 h daily during 14 day) had a limited impact at the whole-plant level but caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…In this investigation, drought stress conditions significantly impaired the growth parameters (shoot and root fresh and dry weights) of both sunflower cultivars (Hysun 33 and FH 598). These results are similar to some earlier findings on radish, cowpea and canola (Shafiq et al 2015, Rebouças et al 2017, Akram et al 2018). However, foliar application with 10 mM trehalose significantly improved these growth parameters of sunflower plants.…”
Section: Discussionsupporting
confidence: 93%
“…In this investigation, drought stress conditions significantly impaired the growth parameters (shoot and root fresh and dry weights) of both sunflower cultivars (Hysun 33 and FH 598). These results are similar to some earlier findings on radish, cowpea and canola (Shafiq et al 2015, Rebouças et al 2017, Akram et al 2018). However, foliar application with 10 mM trehalose significantly improved these growth parameters of sunflower plants.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, plant biomass and lengths of root and shoot of safflower plants were reduced due to drought stress. This is analogous to the findings of Aziz et al [42] in quinoa, Reboucas et al [43] in cowpea and Jabeen et al [44] in spinach, in which a significant reduction in growth was observed in safflower plants due to minimal water supply. They found that obstruction in water supply could affect the rate of transpiration and water-use efficiency, cause lipid peroxidation and nutritional and hormonal imbalances.…”
Section: Discussionsupporting
confidence: 90%
“…Long-range transport events may carry precursor pollutants over long distances outside of industrial areas, and even over distances of intercontinental and hemispheric scales [24,25,26]. Current concentration of tropospheric O 3 significantly reduce photosynthesis and productivity on scales from individual plants to ecosystems, and lead to global crop yield losses and reduced terrestrial net primary productivity [23,27,28,29,30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%